Compliment responses in the drama “Twenty Five Twenty One” (스물 다섯 스물 하나) : pragmatic studies - Disha Aulia Fatikha (Universitas Pendidikan Indonesia (UPI), 2023)
Without even realizing it, language is a common tool we employ in social interactions to interact and communicate. This suggests that humans communicate with one another through language. This research aims to find a compliment response to the drama